Review: Rome and Byzantium in the Visigothic Kingdom: Beyond "Imitatio Imperii," edited by Damián Fernández, Molly Lester, and Jamie Wood. - Devlin, Rebecca A. (Studies in Late Antiquity)
This volume, resulting from a 2019 Princeton workshop, examines how the Visigothic Kingdom in Iberia engaged with Roman and Byzantine imperial models beyond simple imitation, emphasizing the plurality and flexibility of "romanitas" (Romanness). Through thirteen chapters, contributors analyze a wide range of primary sources—including legal codes, hagiographies, and material culture—to reveal the strategic and innovative ways Visigothic rulers and elites shaped political, religious, and economic institutions in Toulouse and Toledo. The work challenges earlier historiographic trends focused on ethnic essentialism and Spanish exceptionalism, highlighting Iberian agency within broader Mediterranean networks. While archaeological evidence is incorporated to some extent, the volume primarily advances late antique scholarship by offering nuanced perspectives on Visigothic rulership, identity, and imperial symbolism.